Contemporary strategies and approaches in 3-D information modeling - Kumar, B. (Bimal) (Engineering Science Reference, 2018)
"This book focuses on three research domains: building information modeling, 3D GIS, and integration of 3D information in the urban built environment. It facilitates the exchange of current scientific information, as well as sharing of state-of-the art technological developments within the AEC industry"--